Web-based Machine Daily Check Application for Preventive Maintenance using Rapid Application Development - Putra, Irga Ramadhan; Butsianto, Sufajar; Raharjo, Sugeng Budi (Journal of Information System Research (JOSH), 2024)
In a manufacturing company, preventive maintenance is one of the scheduled programs implemented to reduce the risk of damage, downtime, and repair costs, thus the production targets can be achieved optimally. So that PT. Trimitra Chitrahasta can become a reliable automotive component manufacturer and be able to compete in the Southeast Asia region in the field of Metal Stamping and Die Making. An integrated maintenance system needs to be developed to increase the achievement of the company's production targets. A web-based information system has been created to support the development of a maintenance system which includes features such as master data image, machine data, and master data person in charge, category, master data description, master data sheet, machine inspection, and daily machine reports. The development methods used are Rapid Application Development (RAD) and Unified Modeling Language (UML) to design business processes. The system implementation uses the Laravel framework PHP, HTML, and MySQL as the database. The analysis results show that the application of a web-based information system can increase the effectiveness of managing preventive machine inspections. The number of documented working days increased significantly, which indicates improved inspection discipline. The frequency of machine downtime was reduced, reducing additional costs for repairs, and mold production target achievement increased from 90% to 100%, indicating increased production efficiency.